2022
DOI: 10.1177/08850666221081757
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Impact of Prone Position on Oxygenation in Mechanically Ventilated Patients with COVID-19

Abstract: Objectives Prone positioning is widely used in mechanically ventilated patients with COVID-19; however, the specific clinical scenario in which the individual is most poised to benefit is not fully established. In patients with COVID-19 respiratory failure requiring mechanical ventilation, how effective is prone positioning in improving oxygenation and can that response be predicted? Design This is a retrospective observational study from two tertiary care centers including consecutive patients mechanically ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 46 publications
(114 reference statements)
0
19
0
Order By: Relevance
“…All included studies were found to be quantitative studies, of which three are retrospective observational studies (casecontrol study) (Parker et al, 2021;Bell et al, 2022;Langer et al, 2021), three analytical observational studies (Stilma et al, 2021;Scaramuzzo et al, 2021;Rossi et al, 2022) and a case study (Taenaka et al, 2021).…”
Section: General Characterization Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…All included studies were found to be quantitative studies, of which three are retrospective observational studies (casecontrol study) (Parker et al, 2021;Bell et al, 2022;Langer et al, 2021), three analytical observational studies (Stilma et al, 2021;Scaramuzzo et al, 2021;Rossi et al, 2022) and a case study (Taenaka et al, 2021).…”
Section: General Characterization Of Studiesmentioning
confidence: 99%
“…The COVID-19 pandemic, which emerged at the end of 2019 (SNS 24, 2022), caused by the new coronavirus SARS-COV-2, can cause severe respiratory infection such as pneumonia.It istends to progress to Acute Respiratory Distress Syndrome (ARDS) (Bell et al, 2022;Scaramuzzo et al, 2021), which according to Fanelli et al (2013) is a clinical syndrome characterized as an acute inflammatory process associated with lung injury, increased vascular permeability, reduced ventilated lung tissue with subsequent onset of acute dyspnea (Costa, D., 2020). The main tenets of ARDS are considered to be: hypoxemia, decreased pulmonary compliance and pathological features of alveolar lysis (hemorrhages, edema and atelectasis).)…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations